2022
DOI: 10.1080/10705511.2022.2096613
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Within × Within and Between × Within Moderation Using Random Intercept Cross-Lagged Panel Models

Abstract: Random-Intercept Cross-Lagged Panel Models allow for the decomposition of measurements into between-and within-person components and have hence become popular for testing developmental hypotheses. Here, we describe how developmental researchers can implement, test and interpret interaction effects in such models using an empirical example from developmental psychopathology research. We illustrate the analysis of Within  Within and Between  Within interactions utilising data from the United Kingdom-based Mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Instead, by specifying random intercepts, the RI‐CLPM captures the trait‐like, individual differences and isolates the dynamic, within‐person effects (Mulder & Hamaker, 2021; Usami, 2021). For this reason, the cross‐lagged effects estimated by RI‐CLPM represent unbiased estimates of within‐person effects, while the covariances between the random intercepts represent the between‐person relationships (Hamaker et al., 2015; Speyer, Ushakova, Blakemore, Murray, & Kievit, 2023). We fitted the RI‐CLPM based on Hamaker et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, by specifying random intercepts, the RI‐CLPM captures the trait‐like, individual differences and isolates the dynamic, within‐person effects (Mulder & Hamaker, 2021; Usami, 2021). For this reason, the cross‐lagged effects estimated by RI‐CLPM represent unbiased estimates of within‐person effects, while the covariances between the random intercepts represent the between‐person relationships (Hamaker et al., 2015; Speyer, Ushakova, Blakemore, Murray, & Kievit, 2023). We fitted the RI‐CLPM based on Hamaker et al.…”
Section: Methodsmentioning
confidence: 99%
“…'s (2015) and Speyer et al. 's (2023) Mplus input code. A more detailed tutorial on this method is included in the Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the traditional approach using a median split, we examined health as a continuous moderator. Based on suggestions by Speyer et al (2023), we used the random intercept of health (RIH) as a time-invariant variable. Specifically, we examined a between (random intercept health) x within (within variables of sickness presence, job satisfaction, or health) interaction to test whether the general health status during the study period moderates the cross-lagged effects of sickness presence on job satisfaction or health and vice versa.…”
Section: General Health Statusmentioning
confidence: 99%
“…Beyond the studies on the between-domain relations, the evidence on relations within the domains of internalising and externalising mental health symptoms is also inconclusive and scarce. In the internalising domain, for example, a study found no longitudinal associations between emotional symptoms (i.e., depressed affect) and peer problems within children [ 28 ], whereas other studies have shown a longitudinal link between peer problems and emotional symptoms [ 29 ]. Some other evidence points toward a reciprocal longitudinal relation only between specific time points [ 30 ].…”
Section: Introductionmentioning
confidence: 99%